PENDIDIKAN AGAMA DAN KARAKTER DI SD/MI DALAM PERSPEKTIF ALQUR’AN - Kosim, Nandang; Solihat, Aan (Staisman Press, 2023)
Character education is an effort to instill good habits so that students are able to behave and act in accordance with the values ​​of good habits that they apply. Character education is an effort to develop the growth of noble character, thoughts, and growth of children. The age of 7-11 years is a golden age for children to accept rational things that are taught by their parents. At this age, it is the right time to teach commendable character to children, so that later they can be attached to their identity. In practice, character education is applied to children through religious teachings. The characters taught are in accordance with the role model of the Prophet Muhammad. This implementation is carried out at home, at school and in the play environment through religious activities, such as congregational prayers, maghrib recitals, Friday taqwa (JUMTAQ) and so on. It is hoped that children can become a generation that excels both in the field of science and technology and their IMTAQ